Seeing Differently: Infinity Pool as a Prototypical Exploration of Perceptual Field Reconfiguration Processes - Ianniello, Antonio; Habets, David (Aisthesis, 2025)
In this article, drawing on an ecological-enactive approach to human cognition, we introduce Infinity Pool, a work-in-progress performance that will serve as a platform for conducting phenomenological and cognitive-behavioral research, ultimately culminating in the development of a 4E Performative Lab. The lab will integrate artistic performance with phenomenological research into a unified event, aiming to establish a unique, real-life instance of collective imagination. Its purpose is to study how we intersubjectively reconfigure the individual perceptual fields during participatory performances. By approaching embodiment not merely as an object of study but as a practical investigation of our bodily engagements with the environment, Infinity Pool, when performed in polluted areas, could prompt us to confront the climate crisis by rendering invisible threats into monstrous forms